Analysis of Lead Levels in Soil Using Silver Amalgam Working Electrode with Anodic Stripping Voltammetry - Yuanita, Hermy
Lead is a type of heavy metal that can cause environmental pollution. Lead pollution in the environment is very dangerous and can cause various health problems in humans. Therefore, an analytical method with high sensitivity to detennine lead in real samples is needed. In this research, voltammetry method is developed to determine lead in real samples using silver amalgam working electrodes. The amalgam formation process on the surface of silver wire was carried out at a deposition potential of -400 m V for 600 seconds. Lead measurements were carried out using a stripping square wave voltammetry technique \\ ith an optimum deposition potential of -1300 m V and an optimum deposition time of 180 seconds. The amalgam working electrode has good repeatability and linear ranges of 10-100 ppb and 100-1000 ppb with a detection limit of 1.7837 ppb. The measurements give results between 444.56 ± 18.4 7 - 577.90 ± I 0.80 mg/kg lead contents in two ::.oil ::.ample::. u::.ing the;: stripping ::.4uare wave voltammetry techni4ue with percent of recovery between 95.9%- 96.2%. The measurement of lead contents in soil samples by voltammetry is compared with AAS measurements that give results between 467.74 ± 11.66 - 607.71 ± 17.06 mg I kg with percent of recovery between 85.9% - 93.6%. The result oft-test (a= 0.05) of the two methods shows that there is no significant differences between the results of the two methods.